A fractal capillary model for multiphase flow in porous media with hysteresis effect. (April 2020) - Chen, He; Chen, Ke; Yang, Minghui; Xu, Peng
Highlights: A fractal pore-throat model with hysteresis is proposed. Darcy's law is extended to consider the non-uniformity of pore cross-section. WRC, RHC, and RAP are derived to describe the retention and transport properties of media porous. The proposed fractal model indicates good consistent with experimental data. Abstract: Multiphase flow in unsaturated porous media exhibiting hysteretic phenomenon is of great significance to oil and gas recovery, agriculture, and hydrology etc. Water retention curve (WRC) and relative hydraulic conductivity function (RHC) as well as relative air permeability function (RAP) are usually employed to characterize the transport properties of porous media. A new fractal capillary model accounting for the hysteresis effect is developed in this paper for the multiphase flow in unsaturated porous media. The analytical expressions for WRC, RHC and RAP under drying and wetting paths are derived accordingly. The proposed fractal capillary model shows good consistent with available experimental results. It has been found that the pore-throat structure in the proposed fractal capillary model takes an important influence on the hysteresis effect and fluid flow, especially for the non-wetting phase. The present work may be helpful for understanding the complex mechanisms of hysteresis effect and transport processes in unsaturated porous media.